Management of School Facilities and Infrastructure Utilization in Improving Learning Quality - Khoirur Rozikin; Juhri Abdul Mu’in; Arman (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to analyze the management of the use of school facilities and infrastructure in improving the quality of learning at SDN 1 Sinar Banten, Ulu Belu District. This study employed a qualitative approach with a descriptive method. Data collection techniques consisted of observation, interviews, and documentation involving the school principal, teachers, and other relevant stakeholders. The findings indicate that the management of facilities and infrastructure at SDN 1 Sinar Banten has not yet been fully optimized to support the improvement of learning quality. Several obstacles were identified, including planning that is not entirely based on an analysis of the school’s actual needs, suboptimal utilization of facilities, irregular maintenance, as well as limited inventory and disposal management. Therefore, increased commitment from all members of the school community is needed to manage educational facilities effectively and sustainably. Keywords: facilities and infrastructure management, learning quality.